RANCANG BANGUN PURWARUPA SISTEM KOMUNIKASI ANTAR KENDARAAN MENGGUNAKAN NRF24L01 MODE SIMPLEX - Adi Wiranata, K. N.; Indra ER, Ngurah; Sukadarmika, Gede (Jurnal SPEKTRUM, 2024)
This research aims to design and develop a prototype vehicle-to-vehicle (V2V) communication system utilizing the NRF24L01 module, ESP32 microcontroller, and OLED display in simplex mode. The system enables effective and instant communication between vehicles in the Vehicle Ad-Hoc Networks (VANETs) environment. In the implementation, we optimized the power transmission level and data rate to ensure fast and responsive data transmission. We integrated key components, such as the ESP32, NRF24L01, and OLED display, into the hardware design to establish a reliable and seamlessly integrated system. We also designed the prototype to minimize costs. The prototype demonstrates an effective and cost-efficient technical solution for vehicle communication, making it suitable for research and development projects requiring wireless communication in real-world vehicle scenarios. This research aims to positively contribute to advancing technology to support connectivity and safety in future vehicle mobility. The findings of this research can be beneficial for researchers, engineers, and policymakers interested in improving vehicular communication and mobility.